Diplomasi Versi Minangkabau - Muhammad Yunis (Politeknik Negeri Padang, 2014)
Pasambahan a Minangkabau society how to speak, the speech full of philosophy which delivery indirectly. This turned out to be complicated understood by some people who did not understand the pasambahan. In the present study, the authors sought to express the values of the philosophy contained in pasambahan as how to speak the traditional Minang community. As time goes, these traditions are disappearing from everyday society, for it needs a way to preserve it back. Pariaman is one area that has always practiced this tradition. In this study, the authors attempted to peel pasambahan text in a manner which according to the author deconstruction approach is one approach that is very controversial in the social sciences today. The process of data analysis by using some theories of social science (eclectic). Among the pragmatic theory and semiotics. The method used in the form of qualitative observation, the authors go directly spaciousness and interact with competent informants. From the discussion, the authors found ten diplomatic elementscontained in tradition and pasamabahan text. These elements in them, '' opener, apology, positioning/element of certainty, stringsattached, request (permission), receipt, delivery destination, contracts/agreements/agreements, offers, and resolver ''.